Peranan SM Entertainment Sebagai Media Diplomasi Publik Korea Selatan di Indonesia - Prawiraputri, Febe Dian Kencana; Andi Meganingratna (Universitas Sulawesi Barat, 2021)
South Korea through Korean wave in music or Korean pop (K-pop) is an example of a country that uses public diplomacy to fulfill its country's interests. K-pop is a popular work by South Korean entertainment agency like SM Entertainment that spreads in various countries ranging from China, Japan, America, and Indonesia. This research aims to examine SM Entertainment's role as a media of South Korean public diplomacy in Indonesia. This research uses the concept of corporate diplomacy and nation branding, using descriptive qualitative research methods. The results of this research show that SM Entertainment provides contribution in the development of South Korean nation branding and serves as a media of South Korean public diplomacy in Indonesia through brand management as one of the agencies that producing K-pop. His role is to turn their brand into nation branding, as a tourism promoter, a constributor in Corporate Social Responsibility, a supporting actor in cultural diplomacy, networking media of investment, and as a representation of South Korean society. This research shows that SM Entertainment's contingency as a pioneer of K-pop brands plays a huge role in the development of South Korean nation branding globally so that it can become a media of South Korean public diplomacy including in Indonesia.